Access 2013 bible - Alexander, Michael, 1950-; Kusleika, Dick (Office Essentials collection, 2013)
A comprehensive reference to the updated and new features of Access 2013 As the world's most popular database management tool, Access enables you to organize, present, analyze, and share data as well as build powerful database solutions. However, databases can be complex. That's why you need the expert guidance in this comprehensive reference. Access 2013 Bible helps you gain a solid understanding of database purpose, construction, and application.